PEMANFAATAN LIMBAH AIR CUCIAN BERAS SEBAGAI PUPUK ORGANIK CAIR UNTUK MENINGKATKAN PERTUMBUHAN TANAMAN TOMAT (Solanum lycopersicum L) - Windi; Ni Made Susun Parwanayoni; Ida Ayu Astarini (Program Studi Biologi Universitas Udayana, 2025)
Washing rice in the rice cooking process produces waste in the form of rice washing water. Rice washing water is kitchen waste which contains nutrients and growth hormones for plants. is an experimental study that aims to explore the content and administration of POC from rice washing wastewater with the addition of molasses and EM4 as organic fertilizer at different concentrations on the growth of tomato plants (Solanum lycopersicum L). Completely Randomized Design (CRD) was used with 4 treatments (P0 = Control (Ordinary water), P1 = 1 liter of rice washing water waste + 100 mL molasses + 100 mL EM4, P2 = 3 liters of rice washing water waste + 100 mL molasses + 100 mL EM4, P3 = 5 liters of rice washing water waste + 100 mL molasses + 100 mL EM4) with 7 replications. The data obtained were analyzed using analysis of variance (ANOVA) with SPSS version 23. The results showed that the POC of rice washing water waste had a significant influence on the height of the tomato plant with 87.57 cm, the number of branches on the tomato plant with 16 branches, the number of fruit with 13 pieces, and the weight of the fruit with the tomato plant with 624.28 g, but had no significant effect on the wet weight and dry weight of the tomato plant. Giving POC concentration to treatment P1 gave the most optimal results compared to other treatments. Keywords: Tomato washing water waste, Liquid Organic Fertilizer